Badalate vāstava āṇi Pu.La. Deśapāṇḍe - Buraṭe, Prakāśa (Lokavāṅmaya Grha, 1982)
Study of the representation of changing social conditions in the writings of Purushottam Lakshman Deshpande, b. 1919, Marathi litterateur.